Technology-driven innovations in financial services: The rise of alternative finance - Lech Gąsiorkiewicz; Jan Monkiewicz; Marek Monkiewicz (Foundations of Management, 2020)
Financial systems worldwide are increasingly experiencing the mounting pressure of the technology-based financial innovations. Some of these developments are generating alternative financial structures existing parallelly to the "old" ones, whereas some others are simply replacing the "old" ones. Alternative intermediating institutions are gaining ground vis-à-vis incumbents, relying on their technological and market supremacy. The space of traditional financial intermediation requires new solutions to be more competitive. Some technological solutions provide additionally for the partial or entire disintermediation of the financial services, thus removing some existing transaction costs and matching directly economic agents. Digitalization and datafication, coupled with artificial intelligence, are offering immense new operational opportunities and economic benefits. On the other hand, they are also the source of new risks to the financial and economic systems, financial stability, national security, and consumer well-being, which need to be properly addressed. We review in this paper principal components of the current stream of technology-based financial innovations and their main drivers, as well as discuss major strategic issues and impacts that we are facing in this area.
Keywords: G21; G22; G23; 650; alternative finance; financial innovations; FinTech; technology enablers; digitalization; financial consumer protection